Predicting Microbiome Function Across Space Is Confounded by Strain-Level Differences and Functional Redundancy Across Taxa - Barnes, Elle M.; Carter, Erin L.; Lewis, J. D. (Frontiers in Microbiology, 2020)
Variation in the microbiome among individual organisms may play a critical role in the relative susceptibility of those organisms to infection, disease and death. However, predicting microbiome function is difficult because of spatial and temporal variation in microbial diversity, and taxonomic diversity is not predictive of microbiome functional diversity. Addressing this issue may be particularly important when addressing pandemic diseases, such as the global amphibian die-off associated with Bd. Some of the most important factors in probiotic development for disease treatment are whether bacteria with desired function can be found on native amphibians in the local environment. To address this issue, we isolated, sequenced, and assayed the cutaneous bacterial communities of Plethodon cinereus along a gradient of land use change. Our results suggest that cutaneous community composition, but not overall diversity, change with changes in land use, but this does not correspond to significant change in Bd-inhibitory function. We found that Bd-inhibition is a functionally redundant trait, but that level of inhibition varies over phylogenetic, spatial, and temporal scales. This research provides further evidence for examining the whole microbial community, including biotic and abiotic interactions, when considering disease dynamics.